Nutrition, Behavior Change and Physical Activity Outcomes From the PEARS RCT—An mHealth-Supported, Lifestyle Intervention Among Pregnant Women With Overweight and Obesity - Ainscough, Kate M.; O'Brien, Eileen C.; Lindsay, Karen L.; Kennelly, Maria A.; O'Sullivan, Elizabeth J.; O'Brien, Orna A.; McCarthy, Mary; De Vito, Giuseppe; McAuliffe, Fionnuala M. (Frontiers in Endocrinology, 2020)
Background: Diet quality and physical activity positively impact pregnancy outcomes among women with obesity, but successful lifestyle interventions require intense clinician time. We aimed to investigate the impact of a behavioural-lifestyle intervention (PEARS) supported by a smartphone app among pregnant women with overweight and obesity, on nutrient intake, behavioural stage-of-change and physical activity. Methods: Pregnant women (BMI 25-39.9kg/m2, measured, n=565) were randomised at 15.6 weeks’ gestation to the intervention (n=278), or a control group (n=287) (ISRCTN29316280). The intervention was grounded in behaviour-change theory. Participants received nutrition (low glycaemic index and healthy eating) and exercise advice, a smartphone app and fortnightly emails. The control group received usual care which does not include dietary advice. At baseline and 28 weeks’ gestation, dietary data were obtained through 3-day food diaries (n=290 matched), and stage-of-change and physical activity data were self-reported. App usage data were collected. Results: There were no differences between the groups at baseline. Compared with the control group, the intervention group had improved dietary intakes post-intervention with; lower glycaemic index (MD -1.75); free sugars (%TE) (MD -0.98); fat (%TE) (MD -1.80); and sodium (mg) (MD -183.49). Physical activity (MET-minutes/week) was higher in the intervention group post-intervention (MD 141.4; 95%CI 62.9, 219.9). The proportion of participants at ‘maintenance’ stage-of-change for physical activity was higher in the intervention group (56.3% versus 31.2%). App use was associated with lower glycaemic index and less energy from free sugars, but not with physical activity. Conclusion: A behavioural-lifestyle intervention in pregnancy supported by a smartphone app improved dietary intakes, physical activity and motivation to engage in exercise.